Middle/Upper Paleolithic interface in Vindija cave (Croatia): new results and interpretations - Karavanić, Ivor (Array, 2006)
Vindija cave is well knows site because it contains fossil hominids associated with Middle and Upper Paleolithic industries. Several publications have discussed Neanderthal remains found with Mousterian industry in level G3 and Upper Paleolithic bone points in level G1. This paper presents recent results of lithic and faunal analysis from transitional levels of the site. Taphonomy of big mammals and hominid bones were examined. Although no human remains were found inside of the faunal assamblage, new results are important for the interpretation of site formation processes and Neanderthal behaviour during transitional period.